Is Targeting the Inflammasome a Way Forward for Neuroscience Drug Discovery?. (December 2018) - Swanton, Tessa; Cook, James; Beswick, James A.; Freeman, Sally; Lawrence, Catherine B.; Brough, David
Neuroinflammation is becoming increasingly recognized as a critical factor in the pathology of both acute and chronic neurological conditions. Inflammasomes such as the one formed by NACHT, LRR, and PYD domains containing protein 3 (NLRP3) are key regulators of inflammation due to their ability to induce the processing and secretion of interleukin 1β (IL-1β). IL-1β has previously been identified as a potential therapeutic target in a variety of conditions due to its ability to promote neuronal damage under conditions of injury. Thus, inflammasome inhibition has the potential to curtail inflammatory signaling, which could prove beneficial in certain diseases. In this review, we discuss the evidence for inflammasome contributions to the pathology of neurodegenerative conditions such as Alzheimer's disease and Parkinson's disease, epilepsy, and acute degeneration following brain trauma or stroke. In addition, we review the current landscape of drug development targeting the NLRP3 inflammasome.